The Dynamics of Lysozyme from Bacteriophage Lambda in Solution Probed by NMR and MD Simulations. Issue 14 (25th June 2013) - Smith, Lorna J.; Bowen, Alice M.; Di Paolo, Alexandre; Matagne, André; Redfield, Christina
Abstract 15N NMR relaxation studies, analyses of NMR data to include chemical shifts, residual dipolar couplings (RDC), NOEs and HN–Hα coupling constants, and molecular dynamics (MD) simulations have been used to characterise the behaviour of lysozyme from bacteriophage lambda (λ lysozyme) in solution. The lower and upper lip regions in λ lysozyme (residues 51–60 and 128–141, respectively) show reduced 1H–15N order parameters indicating mobility on a picosecond timescale. In addition, residues in the lower and upper lips also show exchange contributions to T2 indicative of slower timescale motions. The chemical shift, RDC, coupling constant and NOE data for λ lysozyme indicate that two fluctuating β‐strands (β3 and β4) are populated in the lower lip region while the N terminus of helix α6 (residues 136–139) forms dynamic helical turns in the upper lip region. This behaviour is confirmed by MD simulations that show hydrogen bonds, indicative of the β‐sheet and helical secondary structure in the lip regions, with populations of 40–60 %. Thus in solution λ lysozyme adopts a conformational ensemble that will contain both the open and closed forms observed in the crystal structures of the protein.